2012
DOI: 10.1080/15321819.2011.591479
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Membrane Morphology and Quantity of Immobilized Protein for the Development of Lateral Flow Immunoassay

Abstract: This study was aimed at gaining a quantitative understanding of the effect of protein quantity and membrane pore structure on protein immobilization. The concentration of immobilized protein was measured by staining with Ponceau S and measuring its color intensity. In this study, both membrane morphology and the quantity of deposited protein significantly influenced the quantity of protein immobilization on the membrane surface. The sharpness and intensity of the red protein spots varied depending on the membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…First, each VFI prototype was constructed using 0.1 μm pore size NC membranes, as the signal intensity can be enhanced with this relatively small pore size. The reasoning for this is that a smaller pore NC membrane has a larger surface area for Ag–Ab binding than a larger pore. , Indeed, our previous studies also confirmed that the 0.1 μm pore size enhanced the signal intensity approximately twofold relative to a 5 μm pore size . Previously, we built a theoretical model to simulate the antigen–antibody binding process inside the nitrocellulose membrane to identify the suitable membrane pore size and sample flow rate to improve the detection sensitivity.…”
Section: Resultsmentioning
confidence: 65%
“…First, each VFI prototype was constructed using 0.1 μm pore size NC membranes, as the signal intensity can be enhanced with this relatively small pore size. The reasoning for this is that a smaller pore NC membrane has a larger surface area for Ag–Ab binding than a larger pore. , Indeed, our previous studies also confirmed that the 0.1 μm pore size enhanced the signal intensity approximately twofold relative to a 5 μm pore size . Previously, we built a theoretical model to simulate the antigen–antibody binding process inside the nitrocellulose membrane to identify the suitable membrane pore size and sample flow rate to improve the detection sensitivity.…”
Section: Resultsmentioning
confidence: 65%
“…The protein adsorptive value increases with the increase of polymer concentration. Thin film with higher polymer content leads to a better protein‐polymer binding affinity, due to the electrostatic interaction . Therefore, the highest protein binding was observed at 1359 ± 101.07 μg cm −3 , which was prepared by using 28 wt % of nylon polymer, whereas, only 994 ± 47.05 μg cm −3 protein binding was observed for nylon film with 16 wt % of polymer (N‐16 film).…”
Section: Resultsmentioning
confidence: 99%